2018
DOI: 10.1080/1331677x.2018.1442236
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting tax revenues using time series techniques – a case of Pakistan

Abstract: The objective of this research was to forecast the tax revenue of Pakistan for the fiscal year 2016-17 using three different time series techniques and also to analyse the impact of indirect taxes on the working class. The study further analysed the efficiency of three different time series models such as the Autoregressive model (A.R. with seasonal dummies), Autoregressive Integrated Moving Average model (A.R.I.M.A.), and the Vector Autoregression (V.A.R.) model. In any economy, tax analysis and forecasting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The immense importance of taxes due to their role in economic development and public welfare has made tax research imperative (Streimikiene, Raheem Ahmed, Vveinhardt, Ghauri, & Zahid, 2018). The academic and public interest in tax avoidance has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…The immense importance of taxes due to their role in economic development and public welfare has made tax research imperative (Streimikiene, Raheem Ahmed, Vveinhardt, Ghauri, & Zahid, 2018). The academic and public interest in tax avoidance has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Cyril [51] forecasted tax revenue and its instability using different techniques ARMA, hybrid forecast models, and GARCH models. Streimikiene, Ahmed [48] apply Autoregressive model (AR with seasonal dummies ARIMA and VAR to forecast volatility in the tax revenue data in Tanzania. Cameron, Spyropoulos [49] reviewed tax revenue, forecasting models.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Streimikiene, Ahmed [48] apply Autoregressive model (AR with seasonal dummies), ARIMA, and the Vector Autoregression (VAR) model for fiscal year 2016-17 forecast for tax revenue of Pakistan revealed that among these models the ARIMA model offers better-predicted values for Pakistan total tax revenues. The study used the conventional method and did not consider instability in the data.…”
Section: Introductionmentioning
confidence: 99%
“…In modern government, taxes play an essential role in their programs and they are a powerful tool for achieving main goals in the economy (Kalaš et al 2018). Collection of taxes allows the government to create maximum development projects for the public interest and improve the basic infrastructure of health, education, as well as people's quality of life (Streimikiene et al 2018). For the optimal design of taxes it is essential to be aware of its built-in revenue capacity which implies that automatic revenues respond to changes in the economy (Sanz-Sanz et al 2016).…”
Section: Introductionmentioning
confidence: 99%